Lifting Bank Secrecy: A Comparative Look at the Philippines, Switzerland, and Global Transparency - Ray Flores (Washington University Global Studies Law Review, 2015)
A global trend towards greater financial transparency has created pressure upon several countries with strict and long-standing bank secrecy laws, including Switzerland and the Philippines, two countries of focus in this note. Countries with such laws in place are increasingly becoming the targets of international groups and global powers seeking financial accountability to combat international crime and corruption, as well as to curb tax evasion through offshore storage of wealth. That this pressure has led to reform of the financial institutions of countries like Switzerland, perhaps the most notorious pioneering country of bank account confidentiality, reflects a broader international movement towards freer global access and sharing of banking information. Part I of this Note will look into the Philippines’ statutes of present controversy: the Foreign Currency Deposit Act, in place since 1974, and the Bank Secrecy Law, in place since 1955. It will then proceed to evaluate recent reform measures to the banking system of the Philippines and consider potential alternative measures in addressing the problems arising from bank secrecy. Part II will discuss the history of banking in Switzerland and its response to foreign pressure to reveal more bank information over the past decade. Facing the threat of punishment, its largest private banks have been forced to reveal the fraudulent practices of individuals and companies holding Swiss bank accounts, and its government has moved towards compliance with global standards of transparency. Although the Philippines and Switzerland differ in their respective roles and impacts in the global marketplace, their common legacies of bank secrecy offer a pathway for comparative analysis in Part III. Finally, Part IV will frame these analyses against the backdrop of an international trend towards financial transparency and a freer market place in response to global economic crisis and recession.
Keywords: Banking; Philippines; Switzerland